2021
DOI: 10.1111/dom.14489
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plasma and urine metabolites associated with empagliflozin in patients with type 1 diabetes

Abstract: Aim To examine the impact of the sodium‐glucose co‐transporter‐2 inhibitor, empagliflozin, on plasma and urine metabolites in participants with type 1 diabetes. Material and Methods Participants (n = 40, 50% male, mean age 24.3 years) with type 1 diabetes and without overt evidence of diabetic kidney disease had baseline assessments performed under clamped euglycaemia and hyperglycaemia, on two consecutive days. Participants then proceeded to an 8‐week, open‐label treatment period with empagliflozin 25 mg/day,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Analysis of urinary metabolites from DKD patients treated with atrasentan revealed that it might prevent the progression of mitochondrial dysfunction (Pena et al, 2017). Similar results were obtained in DKD patients treated with sodium glucose cotransporter 2 (SGLT2) inhibitors, such as dapagliflozin, canagliflozin, and empagliflozin (Liu et al, 2020;Liu et al, 2021). Currently, there are no studies investigating the effect of EAR antagonists or SGLT2 inhibitors on the mitochondrial function of podocytes.…”
Section: Targeting Mitochondrial Dysfunctionmentioning
confidence: 67%
“…Analysis of urinary metabolites from DKD patients treated with atrasentan revealed that it might prevent the progression of mitochondrial dysfunction (Pena et al, 2017). Similar results were obtained in DKD patients treated with sodium glucose cotransporter 2 (SGLT2) inhibitors, such as dapagliflozin, canagliflozin, and empagliflozin (Liu et al, 2020;Liu et al, 2021). Currently, there are no studies investigating the effect of EAR antagonists or SGLT2 inhibitors on the mitochondrial function of podocytes.…”
Section: Targeting Mitochondrial Dysfunctionmentioning
confidence: 67%
“…11,12 The kidney and cardiovascular outcome of the patients with T2DM that received Empa treatment was also evaluated in those clinical trials. 13 Though some studies had illustrated the plasma and urine metabolites associated with Empa treatment, 14 the effects of Empa on the metabolism of heart tissue in T2DM are still not known.…”
Section: Introductionmentioning
confidence: 99%
“…SGLT2i are currently not indicated in type 1 diabetes. Although reassuring results have been reported from the SGLT2i experience in patients with type 1 diabetes [42], the available level of evidence is insufficient to permit the use of SGLT2i in this population.…”
Section: Patients With Hf Eligible For Sglt2i Therapymentioning
confidence: 99%